Implementation of Intensified Tuberculosis Case Finding among People Living with HIV in Kampala, Uganda: A cross sectional study - David Okello; Angela Nakanwagi Kisakye; Justine Namakula; Esther Buryegyeya (Journal of Interventional Epidemiology and Public Health)
Introduction: Intensified Case Finding (ICF) is a cost-effective strategy for tuberculosis (TB) control and improving quality of life however, its implementation by health workers is generally reported as low in Uganda. There is limited information on the level of ICF implementation and the barriers or facilitators to its implementation among public health facilities in Kampala Capital City Authority (KCCA). In this study we determined the level of ICF implementation, facilitators and its barriers in KCCA public health facilities.